Enhanced resistance of mice to bacterial infection induced by recombinant human interleukin-1a. - Ozaki, Y (1987)
The effect of recombinant human interleukin-1a on the survival rate of Std-ddY male mice systemically infected with Pseudomonas aeruginosa 12 or Klebsiella pneumoniae P-5709 was evaluated. In P. aeruginosa infection, interleukin-1a given intramuscularly twice, 3 days and 1 day before inoculation of bacteria, most effectively protected animals from death due to infection. The effect was dose dependent, with a maximum survival rate of 92.5% at 10 micrograms per mouse, while only 8.3% of the control group survived until the end of the observation period. The 50% effective dose of interleukin-1a was 0.261 microgram per mouse. In K. pneumoniae infection, interleukin-1a given intramuscularly twice, simultaneously with and 1 day after the inoculation of bacteria, was most effective. The protective effect of interleukin-1a was again dose dependent and was generally more marked than in P. aeruginosa infection. The 50% effective dose was 0.034 microgram per mouse. In both infections, there was no significant increase in the survival rates of animals injected with human albumin or heat-inactivated interleukin-1a. These observations raise the possibility that human interleukin-1a could serve as a therapeutic tool for patients with bacterial infections.